Prostate Cancer Screening: Is it Recommended in 2024? - Thwaini, Dr. Ali (Journal of the Faculty of Medicine Baghdad, 2024)
As we are living the month of Men’s Health awareness, November, we thought of touching base regarding screening for prostate cancer; an intriguing topic indeed, and the jury is out as of yet regarding whether to formalize a screening platform for prostate cancer. The fact remains that prostate cancer is one of the most common cancers in men, and the fifth leading cancer related death globally